Enrichment of eucalyptus oil nanoemulsion by micellar nanotechnology: transdermal analgesic activity using hot plate test in rats’ assay - Abdul Aziz, Zarith Asyikin; Mohd Nasir, Hasmida; Ahmad, Akil; Mohd Setapar, Siti Hamidah; Ahmad, Hafandi; Mohd Noor, Mohd Hezmee; Mohd Rafatullah; Khatoon, Asma; Kausar, Mohd Adnan; Ahmad, Irfan; Khan, Shahida; Al-Shaeri, Majed; et al. (Nature Publishing Group, 2019)
Eucalyptus globulus is an aromatic medicinal plant which known for its 1,8-cineole main pharmacological constituent exhibits as natural analgesic agent. Eucalyptus globulus-loaded micellar nanoparticle was developed via spontaneous emulsification technique and further evaluation for its analgesic efficacy study, in vivo analgesic activity assay in rats. The nanoemulsion system containing Eucalyptus-micelles was optimized at different surfactant types (Tween 40, 60 and 80) and concentrations (3.0, 6.0, 9.0, 12.0, 15.0, and 18.0 wt. %). These formulations were characterized by thermodynamically stability, viscosity, micelles particle size, pH, and morphology structure. The spontaneous emulsification technique offered a greener micelles formation in nanoemulsion system by slowly titrated of organic phase, containing Eucalyptus globulus (active compound), grape seed oil (carrier oil) and hydrophilic surfactant into aqueous phase, and continuously stirred for 30 min to form a homogeneity solution. The characterizations evaluation revealed an optimized formulation with Tween 40 surfactant type at 9.0 wt. % of surfactant concentration promoted the most thermodynamic stability, smaller micelles particle size (d = 17.13 ± 0.035 nm) formed with spherical shape morphological structure, and suitable in viscosity (≈2.3 cP) and pH value (6.57) for transdermal purpose. The in vivo analgesic activity assay of optimized emulsion showed that the transdermal administration of micellar nanoparticle of Eucalyptus globulus on fore and hind limb of rats, possessed the central and peripheral analgesic effects by prolonged the rats pain responses towards the heat stimulus after being put on top of hot plate (55 °C), with longest time responses, 40.75 s at 60 min after treatment administration. Thus, this study demonstrated that micellar nanoparticle of Eucalyptus globulus formed in nanoemulsion system could be promising as an efficient transdermal nanocarrier for the analgesic therapy alternative.